Multimedia Development Corporation As A Service Provider For MSC Status Companies: A Survey On Customer Satisfaction - Siddiqi, Mohammad Irfan (2002)
Cusomer satisfaction is considered to be one of the most important competitive factors for the future and one of the best indicators of a firm's future profits. To date, no research has focused upon the critical determinants of customer satisfaction in multimedia or information technology industry. Therefore, it is becoming important and necessary for researcher to explore into the critical and valid determinants for measuring customer satisfaction in Multimedia Development Corporation(MDC). The study main focus it find out the most essential elements and dimensions those contribute to the customer satisfaction in MDC. Apart from that the study also seeks out the rate of quality level of the services provided by MDC.